Is There a Possible Association between Dietary Habits and Benign Paroxysmal Positional Vertigo in the Elderly? The Importance of Diet and Counseling - Schultz, Adriane Rocha; Neves-Souza, Rejane Dias; Costa, Viviane de Souza Pinho; Meneses-Barriviera, Caroline Luiz; Franco, Pricila Perini Rigotti; Marchiori, Luciana Lozza de Moraes (International Archives of Otorhinolaryngology, 2015)
Introduction Poor diet habits and inadequate intake of nutrients are a concern in the elderly. Nutritional education with guidance may improve the results of the treatment of vertigo.Objective Evaluate the presence of benign paroxysmal positional vertigo (BPPV) associated with feeding habits.Methods Cross-sectional study with elderly people living independently. We evaluated nutritional habits through the method of dietary 24-hour recall and manipulation of Dix-Hallpike.Results Based on a sample of 487 individuals, 117 had BPPV. Among the 117 elderly patients with BPPV, 37 (31.62%) had inadequate feeding. From those 370 individuals without BPPV, 97 (26.21%) had inappropriate feeding. No significant association between nutritional habits and BPPV in the total population was observed (p = 0.3064). However, there was significant relation between BPPV and inadequate carbohydrate intake (p = 0.0419) and insufficient fiber intake (p = 0.03), and the diet of these subjects was rich in polyunsaturated fatty acids (p = 0.0084).Conclusion These data correlate with the dyslipidemia and hypertriglyceridemia status, making it extremely important to reduce the intake of fats and carbohydrates and increase the fiber intake to stabilize triglycerides and thus minimize harmful effects on the inner ear. Food readjustment is suggested in patients with BPPV, along with the work of a multidisciplinary team to improve the quality of the elderly.
Keywords: dizziness; aging; nutrition